Feasibility Study of Flyover Project on R.A. Basyid Street – Untung Suropati Reviewed in Terms of Traffic and Economic Engineering - Hutagalung, Alfrido; Sulistyorini, Rahayu; Herianto, Dwi (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2021)
AbstractTraffic jam is a problem that always exists as an area develops, especially at the Untung Suropati intersection in Bandarlampung City. To solve the problem, a fly over is built and a feasibility study is needed.Feasibility studies conducted are reviewed in terms of traffic performance using pkji method. In terms of economy, it is reviewed from BCR and NPV parameters by analyzing saving of vehicle operating costs variables and Vehicle Travel Time Value.With the development, the degree of saturation for the direction of Labuhan Dalam – Labuhan Ratu decreased from 0.57 to 0.32, for the direction of Labuhan Ratu – Labuhan Dalam reduced from 0.66 to 0.32, for way Halim – Rajabasa reduced from 0.80 to 0.41 and for rajabasa direction – Way Halim reduced from 0.82 to 0.46 so it is said to be feasible in terms of traffic performance. In terms of economy obtained bcr value is 10,059 and NPV is Rp 398,062,846,073.96. So in terms of economics it is said to be feasible.Keywords: Feasibility, Flyover, Traffic jam